Gambaran fraktur elbow pada anak-anak di RSUP Sanglah tahun 2012-2013 - Ketut Arya Surya Pranata; IGST Ngurah Wien Arnaya (DiscoverSys Inc., 2019)
Introduction: Fracture is a loss of bone continuity, either total or partial, usually caused by trauma. Fractures in children are more common due to the immature musculoskeletal system, this is because the child is more susceptible to tears on joint surfaces, epiphyseal plates, aphophyseal insertion of large tendon muscle units. This study aims to determine the prevalence of elbow fracture in children at Sanglah Hospital Denpasar in 2012 until 2013.Method: Study design using cross-sectional method, evaluating the characteristics of elbow fracture in children at Sanglah General Hospital in the period 2012 to 2013.Results: Males tend to have more elbow fractures compared with females with a 73% proportion, based on the cause of overall fracture of the sample due to falling during activity, based on the fracture type Â more subjects experiencing fractures of the supracondylar humerus fracture compared with olecranon fractures as much as 93%.Conclusion: The prevalence of elbow fracture in children in Sanglah General Hospital in 2012-2013 is 15 cases, all caused by falling during the activity. The type of elbow fracture found in most children is a supracondylar humerus fracture.